Clustering scheme of base stations cooperation based on maximizing the average system performance - Kun LI; Kai-zhi HUANG; Jiang JI; Tao FENG; Yan-qing JIN (Tongxin xuebao)
A novel clustering scheme based on maximizing average system performance was proposed.Firstly,according to the probability distribution of signal-to-interference-ratio (SIR)gain of base stations cooperation the average SIR gains were obtained.Then,the cluster structure was generated in the standard of maximizing the average system performance.Not only the average system performance was guaranteed but also the influence of CSI distortion was decreased,while the overall cost was reduced.Simulation results show that when the factors of CSI distortion and channel vibration both are 0.3,the proposed scheme provide a 0.7bit/s/Hz/cell increase of the average system performance compared with the benefit-tree clustering scheme.